KUALITAS PELAYANAN JASA DAN RELATIONSHIP MARKETING SERTA PENGARUHNYA TERHADAP KEPUASAN DAN LOYALITAS PERUSAHAAN PENGGUNA JASA KEAMANAAN - Iin Surtiah (STIA Bagasasi, 2022)
Customer loyalty has not been optimal due to customer satisfaction which is still not optimal due to the lack of good service quality and relationship marketing. The purpose of this study was to determine the effect of service quality and relationship marketing on the satisfaction and loyalty of companies using security services at Red Guard Security Bandung. This research was conducted with a sampling study at the company's partner Red Guard Security Bandung. The research method used is path analysis. (path analysis). The total number of respondents was 67 people. Based on the results of research and data processing, it can be seen that the Service Quality variable (X1) has a Direct influence of 32.40%, and the Indirect influence through its relationship with Relationship Marketing (X2) is 10.20%, so the total effect is 42.60%. The relationship Marketing variable (X2) has a direct effect of 18.60%, and the indirect influence through its relationship with service quality (X1) is 10.20% so the total effect is 28.80%. The results of the calculation of the coefficient of determination (r squared) expressed in percentages describe the contribution of all independent variables, namely Service Quality (X1), Relationship Marketing (X2) to Customer Satisfaction (Y) amounting to 71.40%. In comparison, the implications of Customer Satisfaction in determining variations in Loyalty (Z) (Y) is 79.60%. Meanwhile, other factors that were not examined and influenced loyalty were at Red Guar Security Bandung, indicated by the value of Pyє = 0.204 or 20.40%. From the results of this study, it is expected that the company will be able to encourage better service quality by improving various aspects of service to create optimal customer satisfaction which will ultimately have an impact on customer loyalty.